Real-world experiments over the Internet: the solar energy e-learning laboratory experience - Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2008)
This paper presents the experience from the operation of the solar energy e-learning laboratory in Cyprus, (http://e-lab.hti.ac.cy), and demonstrates the benefits of remote engineering in the field of solar energy. The aim of the solar energy e-learning laboratory (Solar e-lab) is to use the Internet as a tool to make the laboratory facilities accessible to engineering students and technicians located outside the e-lab premises. In this way, the solar energy elearning lab, its equipment and experimental facilities are available and shared by many people, thus reducing costs and widening educational experiences.
Keywords: Collector efficiency; E-learning; Real world experiments; Solar energy